Response and Environmental Care Character of Elementary School Students Results of Implementation of E-Module Based on Local Wisdom Mangrove Ecotourism - Syahrial, Syahrial; Asrial, Asrial; Kurniawan, Dwi Agus; Kiska, Nurul Delima (Universitas Pendidikan Ganesha, 2021)
This study aims to determine the relationship between environmental care character indicators that are integrated with an electronic module based on local wisdom of mangrove ecotourism. The research method uses associative quantitative research, which aims to connect an indicator. The sample in this study was the fourth grade students of IV totaling 22 people, the sampling technique was purposive sampling. The data collection instrument used was a questionnaire, where the questionnaire. The results of the research questionnaire can be said to be valid if the questions in the research questionnaire are able to reveal something to be measured. Data analysis uses descriptive statistics, to analyze data by describing or describing the data that has been collected. The results in this study are that the environmental care character possessed by students has a good category, seen from the environmental care character indicator after using an electronic module based on local wisdom, strengthened by the correlation results obtained by 0.885 and produces a very good relationship, where in using the electronic module has a close relationship with the character of caring for the environment.Â